Z prehistorii Muzeum Archidiecezjalnego w Poznaniu Ein unbekanntes Posener Museum - Kronthal, Arthur (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
Arthur Kronthal, who served as a member of the Poznań city council in the years 1906-1918, was the author of numerous contributions to the history of 19th century Poznań. Among others he was the author the text presented here, which appeared in 1911 in the monthly “Aus dem Posener Lande”. It is the oldest account of what later came to be called the Archdiocesan Museum in Poznań. This is the prehistoric part of the history of this institution.